Historical analysis of mezcals and their current situation from an eco-marxist approach - Plascencia de la Torre, María Fernanda (2018)
This article analyzes the history of production, consume and commercialization of distillate agave manufactured in Mexico, through Political Ecology, from an eco-marxist approach. The main argument is that those artisans whose practices are diverse and heterogeneous, are systematically and legitimately excluded and stripped of the agaves and the associated knowledge to elaborate mescal, to favor industrial production linked to the accumulation of capital. Through historical analysis, with particular emphasis on the second half of the twentieth century to the present, the main changes in their conditions and means of production are defined. The transformation from use value to exchange value and the mutation of the agaves to fictitious commodities are examined. Finally, the article discusses the political and legal schemes used contemporarily by the Mexican State to legitimize exclusion and dispossession.